Interdependency and reliability in Malaysia-China relations amidst the balance of threat - Mohamad ikhram, M. R; Dg junaidah, A. J; Noraini, Z; Zaharul, A (Quantum Academic, 2024)
The decision to cancel several mega projects, such as the construction of the Kuala LumpurSingapore high-speed railway (HSR), the renegotiation of the cost of building the East Coast Railway Route (ECRL), Belt Road Initiative (BRI), and the grey zone issue in the South China Sea, has created tensions between Kuala Lumpur and Beijing. Mahathir's action, which sees the initiative as a new form of Chinese colonization of weak powers, has undermined China's initiative to make Malaysia a strategic hub under ASEAN's One Belt, One Road (OBOR) plan. China has taken action by suspending any form of cooperation and investment in Malaysia to reassess Kuala Lumpur's foreign policy towards Beijing under the Mahathir-led government. However, Mahathir has re-evaluated the initial decision to cancel the screened cooperation projects by holding negotiations on several mega-projects, the BRI issue, and the increase in China's military power in the South China Sea. The decision that Mahathir had anticipated had a significant impact on why Malaysia increased its confidence and cooperation with China despite facing national security threats. This study applies the concept of threat balance. The study's findings indicate that the trend of Malaysia-China bilateral cooperation relations is influenced by reciprocity and mutual trust. Second, the individual's leadership in identifying the context of threats and opportunities also influences bilateral relations between the two countries. Thirdly, the concept of threat balance highlights the anomalies in Malaysia-China relations. The concept of threat balance can predict Malaysia's response and attitude to China based on factors such as threats, risks, and opportunities. Fourth, economic, political, and diplomatic harmony necessitates "reciprocity and credibility" in accordance with international order.